107 Quality Improvement in Action! The Development of a Delirium Bay. (16th September 2019) - Loughlin, Elaine; Conry, Miriam; Gavin, Catherine; Sheil, Orla; O'Connor, Martina; Comer, Anne; O'Connell, Karen; Kearns, Caroline; Mulkerrin, Eamon; Canavan, Michelle; Robinson, Stephanie
Abstract: Background: As illustrated in a cross-sectional study at a Galway hospital, delirium is common with a 29% incidence in hospitalised older adults. This is associated with adverse clinical outcomes. Guidelines support specialised environments in the management of delirium to reduce morbidity and mortality. A delirium bay is a specialised unit with a standardised approach to comprehensive geriatric assessment for older adults with delirium. Methods: We aimed to improve the care of the delirious older adult within our existing framework by creating a 'Delirium Bay' utilising the principles of quality improvement. An interdisciplinary team completed 'Quality Improvement in Action' training run by the Royal College of Physicians of Ireland from October 2018-March 2019. This involved defining our problem statement and 'SMART' aim (Specific, Measurable, Achievable, Realistic, Timely). Measures for improvement included the rate of adverse events, the duration of episodes, patient/family satisfaction, and the use of one-to-one supervision of patients. Results: Stakeholder analysis included nursing, catering, multidisciplinary and healthcare assistance staff. We liaised with hospital management regarding restructuring staffing and maintenance regarding environmental changes. An educational programme on delirium was delivered.. We collected baseline data utilising the 'Plan, Do, Study, Act' Model and utilised this to guide our changes. A Standard Operating Procedures document was drafted. We opened our four-bedded delirium bay on 11 th March 2019. Preliminary data indicates improved management of delirium with preserved continence, reduced risk of falls and high patient and family satisfaction levels. Interventions have been implemented with minimal funding and infrastructural changes. Staffing reconfiguration involved standardised planning replacing a pre-existing ad-hoc system. Conclusion: Delirium in hospitalised older adults is common and associated with increased morbidity and mortality, yet amenable to interventions. We demonstrate that a delirium bay can be set up with a quality improvement approach. Pilot data suggests improved management of these patients within the framework of existing resources. Further collection of data on clinical outcomes is ongoing.